2018
DOI: 10.1002/erv.2621
|View full text |Cite
|
Sign up to set email alerts
|

Testing the addictive appetite model of binge eating: The importance of craving, coping, and reward enhancement

Abstract: In the current study, we examine components of the "addictive appetite" model of recurrent binge eating. Specifically, we tested the influence of addictive processes and the influence of emotional regulation processes on recurrent binge eating behaviour. We recruited 79 women in total for the current study: 22 with bulimia nervosa, 26 weight-matched lean comparison women, 15 women with binge eating disorder, and 16 weight-matched overweight/obese comparison women. Participants completed questionnaire assessmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Subjective stress and cortisol levels are known to be highly related to eating behaviour in healthy women (Epel, Lapidus, McEwen, & Brownell, 2001), and play an even more dominant role in the motivation of eating behaviour in women with bulimia nervosa and binge eating disorder (Leslie, Turton, Burgess, Nazar, & Treasure, 2018). The aim of the current study was to explore the impact of the administration of oxytocin on both reward and anxiety-related processes.…”
Section: Abstract: Oxytocin; Bulimia Nervosa; Binge Eating Disorder;mentioning
confidence: 99%
“…Subjective stress and cortisol levels are known to be highly related to eating behaviour in healthy women (Epel, Lapidus, McEwen, & Brownell, 2001), and play an even more dominant role in the motivation of eating behaviour in women with bulimia nervosa and binge eating disorder (Leslie, Turton, Burgess, Nazar, & Treasure, 2018). The aim of the current study was to explore the impact of the administration of oxytocin on both reward and anxiety-related processes.…”
Section: Abstract: Oxytocin; Bulimia Nervosa; Binge Eating Disorder;mentioning
confidence: 99%
“…Second, FCQ-T scores are associated with eating disorders and obesity. Specifically, individuals with bulimia nervosa and binge eating disorder have higher FCQ-T scores than individuals without eating disorders, and individuals with obesity have higher FCQ-T scores than individuals with normal weight [35][36][37][38]. Of note, however, is that the association between the FCQ-T and (binge-related) eating disorders is much stronger than the association with obesity and, similarly, the positive correlation between FCQ-T scores and body mass index is usually small (e.g., [13,39]).…”
Section: Validitymentioning
confidence: 99%
“…Another study found some overlap between the symptoms of food addiction and BED, however only when addictive traits in binge-type eating disorders are present (67) . This has been described as an addictive appetite model of binge-eating behaviour (68) . The research today suggests that addictive-like aspects of eating may be present in some eating disorder variants.…”
Section: Overlapping Prevalence Ratesmentioning
confidence: 99%